(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
A healthy and credible legislature is indispensable for representative liberal democratic governance. While representation involves informing and listening to those represented and making decisions and exercising influence on their behalf, legislative institutions of many African countries lack the effectiveness to inform and interact with their constituents, thus resulting to serious citizens-representatives disengagement. This pervasive contemporary estrangement is manifested in public cynicism towards political institutions and a collapse in once-strong loyalties and attachment between citizens and government. This research paper draws from case analysis and literature search to examine the potentials and challenges of e-parliament for re-engaging the electorate in the democratic states of Africa. Findings reveal that by leveraging on the exponential growth of ICTs particularly, in the continent, e-parliament provides new strategies for increasing and strengthening deliberative and interactive dialogue between citizens and their representatives. With e-parliament, citizens-representatives estrangement is reduced and new forms of engagement and collaboration created thus making democratic processes more inclusive and transparent. In this process the crisis of democratic legitimacy and accountability is averted for the African states. Though the realization of the full potential of e-parliament in Africa is greatly hampered by such challenges as inadequate infrastructural facilities and capacity building, this paper argues that with effective ICT strategic planning and management so as to judiciously utilize available resources and a mechanism for ICT skill training and development for all stakeholders, e-parliament presents a glimmer of hope for responsive and accountable governance in Africa.